Analysis on acoustic performance and flow field in the split-stream rushing muffler unit. (15th September 2018) - Zhang, Yongan; Wu, Pei; Ma, Yanhua; Su, He; Xue, Jing
Abstract: Airflow velocity is a dominant factor of influencing exhaust resistance and turbulence noise in exhaust muffler of internal combustion engine. In this paper, a new principle of reducing the airflow velocity, based on split-stream rushing in muffler, was proposed. The main idea of this principle is to split the exhaust airflow into two streams first, and then lead them rushing when meeting from two opposite-located holes so that achieve the result of reducing the exhaust airflow velocity through the muffler. The basic structure of the split-stream rushing muffler unit was presented and its acoustic performance was analyzed by using the acoustic wave theory. Finally, the numerical simulation and experimental way were used to verify the internal sound field and velocity changes in the new muffler unit. The results show that the proposed muffler unit can effectively reduce the exhaust airflow velocity through the silencer and exhaust backpressure. Highlights: This paper presents a new type of noise reduction mechanism, named the split-stream rushing muffler unit. The exhaust airflow velocity of the internal combustion engine can effectively be reduced through the split-stream rushing muffler mechanism. The new structure has smaller exhaust backpressure and turbulent kinetic energy than the traditional structure with similar noise reduction performance. The split-stream rushing mechanism provides a new idea for muffler design.